The dynamics of sexual risk amongst South African youth in age-disparate relationships - Qoza, Phiwokazi; van Heerden, Alastair; Essack, Zaynab (Frontiers in Reproductive Health, 2023)
South Africa has the highest burden of HIV in the world with over 8 million people living with HIV. Throughout the epidemic, young women and girls have remained at high exposure to HIV, and account for a quarter of new HIV infections while making up only 10 percent of the population. A key driver of this risk has been transactional and survival sex within intergenerational relationships between adolescent girls and young women and older men (“sugar-daddies” to blessers). We conducted a qualitative study with purposively selected mixed-gender participants aged 16-24 years old from KwaZulu-Natal in age disparate relationships. Themes found through IPA are organized as follows; 1) Navigating Dating: Narratives that show a strong preference for being in an age-disparate relationship; challenges faced when choosing a blesser as a side partner; social media applications seen as creating opportunities to meet side partners 2) The distribution of love and trust in a multi-party sexual network: Condom mis(use) differentiates between straights and sides; eye-test seroguessing. This research offers an understanding of how schemas of non-condom-use are organised. Whereas condom-less sex is often viewed as essential to building social capital in a serious relationship, it is not only the presence or absence of condoms during sex that determines sexual relationship power. Prior to the point of condom use negotiation, eye-test seroguessing, the praxis of testing people visually for HIV, is relied on as a perceived safe sexual practice behaviour. Seroguessing, not only develops consortium (trust, reciprocity, and solidarity) during casual sex, but sustains it in longer term relationships with parties who do not test together nor validate their HIV status together. Eye-test seroguessing delineates safe sexual partners instead of testing and validating by determining what HIV looks like. This potentially elevates HIV acquisition risk for all those who belong to the multi-party sexual networks that are founded on it. Therefore, it is probable that the eye test seroguessing is a key factor for why South Africa has not achieved the desired Incidence to Prevalence Ratio (IPR) threshold in its response to HIV/Aids epidemic.